Significant Differences in IBD Care and Education across Europe: Results of the Pan-European VIPER Survey - Kral, Jan; Nakov, Radislav; Lanska, Vera; Barberio, Brigida; Benech, Nicolas; Blesl, Andreas; Brunet, Eduard; Capela, Tiago; Derikx, Lauranne; Dragoni, Gabriele; Eek, Aileen; Frias-Gomes, Catarina; et al. (Digestive diseases (Basel, Switzerland), 2023)
BACKGROUND: Inflammatory bowel disease (IBD) care and education might differ around Europe. Therefore, we conducted this European Variation In IBD PracticE suRvey (VIPER) to investigate potential differences between countries. METHODS: This trainee-initiated survey, run through SurveyMonkey®, consisted of 47 questions inquiring basic demographics, IBD training, and clinical care. Results were compared according to gross domestic product (GDP) per capita, for which countries were divided into 2 groups (low/high income, according to the World Bank). RESULTS: The online survey was completed by 1,285 participants from 40 European countries, with a majority of specialists (65.3%) working in academic institutions (50.4%). Significant differences in IBD-specific training (55.9% vs. 38.4%), as well as availability of IBD units (58.4% vs. 39.7%) and multidisciplinary meetings (73.2% vs. 40.1%), were observed between respondees from high and low GDP countries (p < 0.0001). In high GDP countries, IBD nurses are more common (85.9% vs. 36.0%), also mirrored by more nurse-led IBD clinics (40.6% vs. 13.7%; p < 0.0001). IBD dieticians (33.4% vs. 16.5%) and psychologists (16.8% vs. 7.5%) are mainly present in high GDP countries (p < 0.0001). In the current COVID era, telemedicine is available in 73.2% versus 54.1% of the high/low GDP countries, respectively (p < 0.0001). Treat-to-target approaches are implemented everywhere (85.0%), though access to biologicals and small molecules differs significantly. CONCLUSION: Much variability in IBD practice exists across Europe, with marked differences between high and low GDP countries. Further work is required to help address some of these inequalities, aiming to improve and standardize IBD care and training across Europe.
Keywords: biologické přípravky; idiopatické střevní záněty; Inflammatory Bowel Diseases; Inflammatory bowel diseases; Quality of care; průzkumy a dotazníky; lidé; Europe; Evropa; Surveys and Questionnaires; European; Biological Products; VIPER; COVID-19; Training; Humans